Antimicrobial Resistance: Is There a 'Light' at the End of the Tunnel? - Leon G. Leanse; Sanjay Marasini; Carolina dos Anjos; Tianhong Dai (MDPI AG, 2023)
In recent years, with the increases in microorganisms that express a multitude of antimicrobial resistance (AMR) mechanisms, the threat of antimicrobial resistance in the global population has reached critical levels. The introduction of the COVID-19 pandemic has further contributed to the influx of infections caused by multidrug-resistant organisms (MDROs), which has placed significant pressure on healthcare systems. For over a century, the potential for light-based approaches targeted at combatting both cancer and infectious diseases has been proposed. They offer effective killing of microbial pathogens, regardless of AMR status, and have not typically been associated with high propensities of resistance development. To that end, the goal of this review is to describe the different mechanisms that drive AMR, including intrinsic, phenotypic, and acquired resistance mechanisms. Additionally, the different light-based approaches, including antimicrobial photodynamic therapy (aPDT), antimicrobial blue light (aBL), and ultraviolet (UV) light, will be discussed as potential alternatives or adjunct therapies with conventional antimicrobials. Lastly, we will evaluate the feasibility and requirements associated with integration of light-based approaches into the clinical pipeline.